FAKTOR-FAKTOR PENENTU TARIF BIAYA AUDIT EKSTERNAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris terhadap Perusahaan yang terdaftar di Bursa Efek Indonesia) - Pradana, Satria Edvan Nanda; Purwanto, Agus (Diponegoro Journal of Accounting, 2016)
This study aims to determine the effect of political connection, CEO’s gender, external auditor’s reliance on internal auditor and firm size towards the audit fees. The population in this study is the all companies listed in Indonesia Stock Exchange in the period 2010 to 2014. Sampling technique used is purposive random sampling. The analytical tool used is multiple linear regression analysis.Based on the results of tests performed can be concluded that: political connection does not affect and insignificant toward the audit fee. CEO’s gender negatively affect and significant toward the audit fee. External auditor’s reliance on internal auditor does not affect and insignificant toward the audit fee. Firm size positively affect and significant toward the audit fee.